MENINGKATKAN KECEPATAN EFEKTIF MEMBACA (KEM) DENGAN MENGGUNAKAN METODE KLOS SISWA - Alimuddin, Muh. Ali (Makassar Journal of Social Sciences, 2015)
Abstract: effective speed reading has a very important role, because with the fast reading and reading comprehension ability of a person qualified to master science and technology. Indonesian reading habits unfavorable impact negatively on the level of legibility of a person or a student. To overcome this much needed effort and creativity of teachers. Klos in the application of the method of learning to read is one way to solve the problem. The research objective of this class action is to increase the Effective Speed Reading (KEM) using methods klos class XI IPA 2 SMA Negeri 3 Makassar. This classroom action research takes place in SMA Negeri 3 Makassar class XI IPA 2, the number of students 40 students. Implementation of the activities carried out through three cycles. Before the first cycle carried out the need for pre-action, namely the identification of methods klos and Effective Speed Reading (KEM), then implemented the first cycle as the application of methods klos, as the implementation of the implementation of the second cycle klos method, and the third cycle as the consolidation phase. Data were analyzed using qualitative analysis that is used for the qualitative data obtained from observations of students and teachers during learning in the classroom, and quantitative analysis used to test Effective Speed Reading (KEM) students by using klos. Results of the study in the first cycle readability level is still low, due to the effective speed average reading rate of 87 words per minute with 18% Independent, Instruktional rate of 38% and 44% in frustration. In the second cycle results of the study experienced a positive change which effectively speeds average reading rate of 150 words per minute with 78% Independent, Instructional rate of 18%, and the frustration level of 4%. Results of the study in the third cycle experienced an average consolidation Effective Speed Reading (KEM) 210 wpm with independent level of 100%. The result showed that the activity of learning to read faster by using klos can increase Effective Speed Reading (KEM) students